Impact of percutaneous coronary intervention on short and long-term prognosis of elderly patients with acute myocardial infarction from 2010 to 2017 in Japanese population. (25th November 2020) - Goto, J; Watanabe, T; Kobayashi, Y; Toshima, T; Wanezaki, M; Nishiyama, S; Otaki, Y; Kutsuzawa, D; Kato, S; Tamura, H; Arimoto, T; Takahashi, H; et al.
Abstract: Background: Advances in therapies have successfully decreased short-term mortality in patients with acute myocardial infarction (AMI). Although aging population is recently increasing in developed countries, there are few reports about the association between prevalence of percutaneous coronary intervention (PCI) and long-term prognosis in elderly patients with AMI in Japan. Purpose: The aim of this study was to clarify the prevalence of PCI and the impact of PCI on short and long-term prognosis of elderly patients with AMI. Methods and results: We investigated the prevalence of PCI and short-term mortality in 4, 109 patients with AMI who were registered in Yamagata AMI Registry from 2010 to 2017. Long-term mortality was investigated using data from death certification in July 2019. We divided patients with AMI into three age groups (group 1, <65 years old; group 2, 65–79 years old; and group 3, ≥80 years old). Short-term mortality within 30 days was 6.5%, 12.1%, and 28.6%, respectively. Also, prevalence of PCI was 88.0%, 84.7%, and 62.7%, respectively. Multivariate analysis revealed that age, PCI, and severity of Killip classification were significantly associated with short-term mortality after adjustment for confound factors in group 3. Since the prevalence of PCI in group 3 was the lowest among three groups, the cause of PCI not being executed was investigated in 1, 429 patients aged ≥80 years old. Elderly patients who didn't undergo PCI was older, more women, and had higher prevalence of chronic kidney disease, previous stroke, and severe Killip classification. Multivariate analysis revealed that age and Killip III/IV were significantly associated with non-executed PCI after adjustment for confound factors. Next, we investigated impact of PCI on long-term mortality in elderly patients who escaped acute death. Multivariate Cox hazard analysis revealed that PCI was associated with lower mortality after adjustment for confound factors (adjusted hazard ratio 2.47, 95% CI: 1.47–4.06; p=0.0008). Conclusion: Lower prevalence of PCI and higher short-term mortality were observed in elderly patients with AMI aged ≥80 years old. PCI ameliorated long-term mortality as well as short-term mortality in elderly patients with AMI. Funding Acknowledgement: Type of funding source: None